HUMAN RIGHTS´ PHILOSOPHY: UNIVERSALISM AND CULTURAL LOCALISM - Grubba, Leilane Serratine; Boff, Salete Oro; Pellenz, Mayara (Revista Brasileira de Direitos Fundamentais & Justiça, 2023)
The research analyzes the clash between universalism and cultural localisms, aiming to carry out an epistemological analysis of the discursive foundation of human rights. We problematize the existence of an apparent dichotomy between universalism and cultural localism. Methodologically, it uses discourse analysis, with an emphasis on deconstructivism. At the discursive level, the research points there is no contrast between universal human rights and different cultural localism. Understanding human rights as a universalized Western culturalism, there is no opposition between them and other cultural localism that contribute to different dimensions of dignity. The research contributes to the field by presenting the discursive element of universal human rights, manifesting its philosophical foundations.